2018
DOI: 10.9745/ghsp-d-18-00041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Family Planning Service Availability and Readiness in 10 African Countries

Abstract: In the 10 countries surveyed, the availability of oral contraceptives, injectables, and condoms varied greatly, and the availability of basic items indicating service readiness, such as guidelines, trained staff, equipment, and certain commodities, was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 6 publications
5
50
2
Order By: Relevance
“…This high demand for implants is consistent with analysis showing that large increases in implant use across sub-Saharan Africa since the early 2000s are driving increased modern contraceptive use in the region 17 . By the mid-2010s, Kenya had the highest prevalence of implant use among 17 sub-Saharan African countries for which such data were available, with the percentage of married women using implants increasing from 2% to 18% between 2008 and 2016 18 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This high demand for implants is consistent with analysis showing that large increases in implant use across sub-Saharan Africa since the early 2000s are driving increased modern contraceptive use in the region 17 . By the mid-2010s, Kenya had the highest prevalence of implant use among 17 sub-Saharan African countries for which such data were available, with the percentage of married women using implants increasing from 2% to 18% between 2008 and 2016 18 …”
Section: Discussionsupporting
confidence: 83%
“…Procuring family planning commodities was a recurring challenge for this project and is a common problem across Africa, especially for FBO-managed facilities 18 . A study of FBO-managed facilities in 13 African countries found that more than half had faced stock-outs of one or more reproductive health products (including contraceptives) in the past 3 months, requiring staff to implement creative solutions such as finding other sources of commodities and purchasing and storing buffer stock 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Strategies aimed at improving the quality of post abortion care by increasing providers knowledge, attitudes and skills and reducing unnecessary restrictive biases were found effective in increasing access to contraception (24,25). In addition, several studies from Togo identi ed multiple service availability and readiness related barriers (26).…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach has been adopted by Kanyangarara et al (2018) to assess obstetric service readiness in 17 low-and middle-income countries (LMICs) [13]. Ali et al (2018) obtained a general service score as the average of domain-specific scores to compare family planning service availability and readiness in 10 African countries [14]. This average composite measure takes into account the different aspects of health facility readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, Burkina Faso has conducted two SARA surveys; in 2012 and in 2014. The data have been used to assess readiness of surgical [20], obstetric [13] and family planning services [14].…”
Section: Introductionmentioning
confidence: 99%